The CARMENES search for exoplanets around M dwarfs: photospheric parameters of target stars from high-resolution spectroscopy. II : simultaneous multiwavelength range modeling of activity insensitive lines - Passegger, Vera Maria; Quirrenbach, Andreas; Henning, Thomas; Kaminski, Adrian (Astronomy and astrophysics, 2019)
We present precise photospheric parameters of 282 M dwarfs determined from fitting the most recent version of PHOENIX models to high-resolution CARMENES spectra in the visible (0.52-0.96 μm) and NIR wavelength range (0.96-1.71 μm). With its aim to search for habitable planets around M dwarfs, several planets of different masses have been detected. The characterization of the target sample is important for the ability to derive and constrain the physical properties of any planetary systems that are detected. As a continuation of previous work in this context, we derived the fundamental stellar parameters effective temperature, surface gravity, and metallicity of the CARMENES M-dwarf targets from PHOENIX model fits using a χ2 method. We calculated updated PHOENIX stellar atmosphere models that include a new equation of state to especially account for spectral features of low-temperature stellar atmospheres as well as new atomic and molecular line lists. We show the importance of selecting magnetically insensitive lines for fitting to avoid effects of stellar activity in the line profiles. For the first time, we directly compare stellar parameters derived from multiwavelength range spectra, simultaneously observed for the same star. In comparison with literature values we show that fundamental parameters derived from visible spectra and visible and NIR spectra combined are in better agreement than those derived from the same spectra in the NIR alone.
Gesehen am 12.03.2020